2015
DOI: 10.1186/s12966-015-0257-6
|View full text |Cite
|
Sign up to set email alerts
|

Young adult males’ motivators and perceived barriers towards eating healthily and being active: a qualitative study

Abstract: BackgroundThere is a lack of understanding of young men’s perspectives in obesity-related research. This study aims to: (1) identify young men’s perceived motivators and barriers in adopting healthy eating and physical activity behaviours, and (2) explore any differences in responses by weight status categories.MethodsTen focus groups (32-63 minutes; 3-9 participants per group) were conducted with 61 young men (BMI: 25.3 ± 5.1 kg/m2, aged: 18-25 years) from the Hunter region, New South Wales, Australia. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
126
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(156 citation statements)
references
References 45 publications
24
126
1
5
Order By: Relevance
“…To align with the PRECEDE aspects of the model [32], a number of steps were taken to understand the social, epidemiological, behavioural and environmental assessments for this population group when developing HEYMAN. Formative research with young men was conducted to identify perceived motivators and barriers for healthy eating and physical activity [17, 35] and to identify their preferences for intervention content and delivery medium [36]. In addition, the program was informed by best practice guidelines for diet [37] and physical activity [38], theoretical guidelines from an integrated framework of Social Cognitive Theory (SCT) [39] and Self Determination Theory (SDT) [40], and evidence from effective health-related interventions in this population [23, 24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To align with the PRECEDE aspects of the model [32], a number of steps were taken to understand the social, epidemiological, behavioural and environmental assessments for this population group when developing HEYMAN. Formative research with young men was conducted to identify perceived motivators and barriers for healthy eating and physical activity [17, 35] and to identify their preferences for intervention content and delivery medium [36]. In addition, the program was informed by best practice guidelines for diet [37] and physical activity [38], theoretical guidelines from an integrated framework of Social Cognitive Theory (SCT) [39] and Self Determination Theory (SDT) [40], and evidence from effective health-related interventions in this population [23, 24].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a media release, with information appearing via the local newspaper, magazines and radio stations. Young men who took part in previous participatory research [17, 35] and who indicated an interest in being contacted via e-mail about future health programs were also invited to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to other research reporting that economics and knowledge impact health behaviors among Black college men. 38-39 Additionally, it has been reported that limited access to healthy food was a barrier to physical activity and healthy eating among college men. 40 Research has also reported that some barriers to healthy eating in young adult males and weight management in males and females were unhealthy food being more accessible and cheaper and the social influence of those around them.…”
Section: Commentmentioning
confidence: 99%
“…40 Research has also reported that some barriers to healthy eating in young adult males and weight management in males and females were unhealthy food being more accessible and cheaper and the social influence of those around them. 38,41 Another study reported one barrier to fruit and vegetable consumption in urban, immigrant Black men was their cost and someone else having to prepare the vegetables. 39 Additionally, it was also reported that a higher knowledge about the recommendations for the number of servings of fruits and vegetables was associated with higher fruit and vegetable consumption.…”
Section: Commentmentioning
confidence: 99%